2016
DOI: 10.17140/tfmoj-1-107
|View full text |Cite
|
Sign up to set email alerts
|

Lambda Cyhalothrin Elicited Dose Response Toxicity on Haematological, Hepatic, Gonadal and Lipid Metabolic Biomarkers in Rat and Possible Modulatory Role of Taurine

Abstract: Extensive application of pesticides is usually accompanied with serious problems of pollution and health hazards. Lambda-cyhalothrin (LCT), a type II synthetic pyrethroid, is widely used in agriculture, home pest control and protection of foodstuff. This study designed to evaluate the dose dependent haematological, hepatic and gonadal toxicity of LCT at different dose levels in Wistar rat. Investigations were also done to find out the toxic effect of lambda cyhalothrin on lipid metabolism in female rat and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
6
2
0
Order By: Relevance
“…In the current study, terminal body weight and relative weight of liver of LCT-intoxicated rats were reduced that run in a good agreement with previous studies [14,[45][46][47][48]. Elhalwagy et al [1] demonstrated that decreasing body weight and organs relative weight is one of the chronic effects of pyrethroids toxicity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the current study, terminal body weight and relative weight of liver of LCT-intoxicated rats were reduced that run in a good agreement with previous studies [14,[45][46][47][48]. Elhalwagy et al [1] demonstrated that decreasing body weight and organs relative weight is one of the chronic effects of pyrethroids toxicity.…”
Section: Discussionsupporting
confidence: 91%
“…Increased serum ALT and AST activities reflect LCTinduced hepatotoxicity, causing these enzymes to leak into blood [51,52]. These observations matched with earlier finding of LCT toxicity in rats [1,8,15,47,53,54]. ALT activity reflects general hepatic damage and AST activity indicates mitochondrial damage; elevated levels of ALP in blood are regarded as an indicator of hepatic necrosis and cholestasis [55,56].…”
Section: Discussionsupporting
confidence: 73%
“…This reduction may be related to enhanced usage of GSH for detoxification of LCT bait-induced free radicals. Our results are in accordance with those of Ghosh et al (2016) who mentioned that LCT causes depletion in GSH content due to its usage to challenge oxidative stress. Superoxide dismutase (SOD) is regarded as the first line of defense against the harmful effects of reactive oxygen species (ROS) in the cell by catalyzing the dismutation of superoxide radicals to produce H2O2.…”
Section: Discussionsupporting
confidence: 93%
“…In our current study, body weight, relative weight of lung of LCT-treated rats were reduced that run in a good agreement with previous studies [44][45][46][47][48][49] . Kohner et al [44] observed that decreasing body weight and organs relative weight is one of the chronic effects of pyrithroids toxicity.…”
Section: Discussionsupporting
confidence: 93%